ASAS KEBEBASAN DALAM BERKONTRAK MENURUT HUKUM ISLAM - Ihsan Aziz (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
What is meant by the principle of freedom of contract or what is often referred to as an open system is the existence of the widest possible freedom by law given to the public to enter into an agreement on anything, as long as it does not conflict with statutory regulations, propriety and public order . The affirmation of the existence of freedom of contract can be seen in Article 1338 paragraph (1) of the Civil Code, which states that all treaties made legally apply as a law for those who make them. It is also intended to state the strength of the agreement, which is the same power as a law. Such power is given to all treaties made lawfully.